The Effects of Entrepreneurial Values and Entrepreneurial Orientation on the Financial Performance: An Empirical Evidence from Indonesian State-Owned Enterprises - Uno, Sandiaga Salahuddin; Supratikno, Hendrawan; Ugut, Gracia Shinta S.; Bernarto, Innocentius; Antonio, Ferdi; Hasbullah, Yudistira (Current Aspects in Business, Economics and Finance Vol. 10, 2023)
The present study focuses on the effect of Entrepreneurial Values and Entrepreneurial Orientation on the Financial Performance of Indonesian State-Owned Enterprises, and it also includes Environmental Dynamism (ED) and Resource Availability (RA) as moderating variables. The study also improves understanding of the impact of Financial Performance on Intention to Sustainable Development (ITS) and Financial Performance on Intention to Collaborate (ITC) in Indonesian state-owned enterprises. The PLS-SEM methodology was used in this study, along with the purposive sampling method. The unit of analysis is all the state-owned enterprises listed that consists of 81 out of 106 state-owned enterprises, while the unit of observation is individuals from those state-owned enterprises (represented by the paired CEO and CFO who are originated from the same company). The implication of the evidence in this study is that the government needs to consider carefully any additional state-capital participation in SOEs so as not to create comfort zone and making firms tend to lose financial discipline and expand to non-core activities that have an impact of reducing their entrepreneurial orientation which may decrease the financial performance.